Contraceptive use: implication for completed fertility, parity progression and maternal nutritional status in Nigeria (2011)
The study identified socio-demographic factors influencing contraceptive use while using nutritional status, completed fertility and parity progression as key variables. NDHS, 2008 dataset on married women aged 45-49 was used. Chi-square, ordinary linear and logistic regression models were used for the analysis. The mean age of the women and CEB were 46.8±1.5 years and 6.9±3.1 respectively. About 26.0% of the women ever used contraception, while 9.0% of the women were underweight. Parity progression from parity 0 to 4 was consistently higher among never-users than women who ever used contraception. The tempo changes for all parities above four as ever-users now progress at lower rate during these periods. The completed fertility and the risk of undernourishment were significantly higher among never users of contraception than ever users. The level of risk persists even when the potential confounding variables were used as control